A Systematic Review: Is Transformational Leadership Effective for Organizational Commitment? - Kristiana, Yustisia; Tukiran, Martinus (Journal of Industrial Engineering & Management Research, 2021)
Transformational leadership has been widely implemented. Transformational leadership can be used to achieve organizational commitments. The purpose of this article is to review the correlation between transformational leadership and organizational commitment, as well as the impact of other variables that strengthen the correlation. This article analyses the research related to the correlation between transformational leadership and organizational commitment, as well as the mediators and moderators that strengthen this correlation. The method consists of systematically reviewing transformational leadership and organizational engagement through journal reviews. This systematic review shows that transformational leadership significantly predicts organizational participation. Transformational leadership influences organizational commitment through intermediary variables, that is, job characteristics and job autonomy. Other results indicate that emotional intelligence is a moderating variable that can strengthen the correlation between transformational leadership and organizational commitment.